APPLICATION OF DIRECT INSTRUCTION WITH LABORATORY ACTIVITY TO IMPROVE STUDENTS’ PARTICIPATION AND LEARNING ACHIEVEMENT - Tonjo, Veronika; Wirjawan, Johannes; Untung, G (PEOPLE: International Journal of Social Sciences, 2017)
This research aimed to improve students’ achievement and participation. To achieve the goals, researchers applied direct instruction model with laboratory activity during teaching and learning process. A qualitative methods was applied in this study in a classroom action research (CAR) framework. Subject of this study were 7 grade students of Stanislaus I Surabaya junior high school. The data were collected by test, observations rubric and questionnaires before and after treatment.The classroom action research was completed in two cycles. Based on the statistical analysis, there was a significant improvement in teaching and learning goals before and after treatment. This result affirm that the use of direct instruction model with laboratory activity in science learning process can improve students learning achievement and participation.